Normalization and Economic Employment of Peace: The New Middle East Project as a Model - Hafeez, Tarek Abdel; Mohammed, Ismail Akbar (The International and Political Journal, 2025)
The limited growth prospects for the Palestinian economy have restricted its ability to meet local market demands for good and services. Consequently, a new reality of forced economic dependency on Israel has emerged, where the market gap in Palestinian territories is filled by Israel’s economic policies in the occupied Palestinian territories have deprived the West Bank and Gaza of any opportunity to export their surplus to neighboring Arab or Islamic countries. At the same time, these polices have obstructed the import of essential production equipment, machinery, and raw materials. Therefore, the fragility of Palestinian developmental conditions, coupled with the ongoing Israeli occupation, has been a key factor in the failure of political solutions such as the Oslo Accords and the 1994 Paris Protocol, which was based on those agreements. This political and economic stagnation in Palestine necessitates the establishment of an alternative framework aimed at achieving social justice, fostering self-reliance, and breaking free from the forced economic coexistence with Israel under a political peace that fails to bring about any real social justice